Frequently exposed to radiation causes thyroid disorder / Nur Farhan Natasha Fadzil ... [et al.] - Fadzil, Nur Farhan Natasha; Ramli, Nurul Annisa; Muhamad Fauzi, Nursuhaila; Mohd Nasir, Nur Azlin Atikah; Hashim, Aimie Rifhan; Kamaruddin, Sharir Aizat; Mat Nazir, Eliy Nazira; Azizan, Muhammad Nashiruddin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Radiation exposure is a global health issue that receives serious attention from the scientific and medical community. In a time of rapid advancement in technology and increased radiation exposure from multiple sources, worries about possible health hazards have become more prevalent. One important area of focus is the effects of frequent radiation exposure on the thyroid gland, an important component of the endocrine system. In general, humans will always be exposed to natural or man-made radiation. Radiation naturally comes from elements from within the earth or cosmic rays from outer space. While medical imaging, food irradiation, and even airport security scanners are man-made radiations that are widely used today. Humans undergoing radiotherapy without proper control or those exposed to radiation at work are the only contributors to thyroid disorders.